Incidence of Die Spacing in the Evolution of Damage in Two-Pass Wire Drawing Processes - Cruchaga-Ssa., M; Gonzalez-Ortega, A (Elsevier Ltd, 2018)
Multipass wire drawing can be made by passing the wire through consecutive dies (tandem configuration) or through dies apart from each other (sequential configuration). In this work, both configurations are simulated with the purpose of determining the effect of die spacing on the development of fractures in two-pass drawn wires subjected to different area reductions. To achieve this, an uncoupled ductile fracture criterion that considers the evolution of damage under conditions of increasing effective plastic deformation and triaxiality occurring in the material is applied and assessed in its ability to predict the beginning of fracture under the two analyzed configurations. The comparison between tandem and sequential configurations allows the extension of the fracture model used in previous work in order to account for the evolution of damage not only under positive triaxiality values but also and simultaneously for positive triaxiality rates during the entire drawing sequence. This new model reproduces in a good way the differences in the damage evolution between both configurations and also allows to explain the reason why the tandem configuration is more unsafe than the sequential one. © 2018 Elsevier Ltd